Determinação das propriedades físicas do solo em função do uso e ocupação em Caçapava do Sul – RS - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The soil must have adequate physical conditions to favor the development of the plants. Concern about soil quality has increased significantly since its use and intense mobilization may result in a reduction in its capacity to maintain a significant production. Management systems that favor vegetation removal, soil exposure, fertilizer and pesticide use, machine traffic and animal trampling alter soil structure and are often cited as causes of physical quality decrease. The objective of this study was to determine the soil quality in the city of Caçapava do Sul, based on the characterization of physical attributes, making a comparative analysis of the same under different uses, such as: soybean and livestock culture (native field). The physical attributes determined were soil density (Ds), particle density (Dp), total porosity and hydraulic conductivity (k). The analyzes were carried out in four replicates, which were conducted in quadriplicate, the results were analyzed through the program Statistica version 7.0. The area used for soybean planting had higher values of soil density, in relation to the density of particles, the native field presented lower value in the more superficial layer, while the field with soybean showed lower result of porosity in the layer of 0.25 a 0.35m, although it did not present statistical difference. Regarding hydraulic conductivity (K), all treatments presented negative results. The results found in this study allow to affirm that the two types of soil analyzed behaved in a similar way in relation to the evaluated parameters.
Keywords: Densidade do solo; Manejo do solo; Porosidade do solo; Key-words: soil density; Soil management; Soil porosity; CNPQ::CIENCIAS EXATAS E DA TERRA